2016
DOI: 10.4103/2231-0762.181167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of platelet-rich plasma and platelet-rich fibrin in alveolar defects after removal of impacted bilateral mandibular third molars

Abstract: Aim and Objectives:This study attempted the evaluation of the efficacy of platelet-rich plasma (PRP) and platelet-rich fibrin (PRF) in alveolar defects after removal of bilateral mandibular third molars.Materials and Methods:A total of 30 patients reporting to Department of Oral and Maxillofacial Surgery and having bilateral mandibular third molar impaction in both male and female aged between 18 and 30 years were included in this study. PRF and PRP were placed in extraction site and recalled at 2nd, 4th, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…So the result of this analysis may affirm the fact that the adjunctive use of PRP together with conventional grafting procedures may be more helpful for the bone repair of periodontal intrabony defects. Nevertheless, quite a lot of studies substantiated a positive impact of PRF on bone healing [ 34 , 35 ]. The inconsistency of the outcomes of studies may be attributed to the differences in the methodologies employed to obtain the PRP/PRF preparations.…”
Section: Discussionmentioning
confidence: 99%
“…So the result of this analysis may affirm the fact that the adjunctive use of PRP together with conventional grafting procedures may be more helpful for the bone repair of periodontal intrabony defects. Nevertheless, quite a lot of studies substantiated a positive impact of PRF on bone healing [ 34 , 35 ]. The inconsistency of the outcomes of studies may be attributed to the differences in the methodologies employed to obtain the PRP/PRF preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The p value was 0.000 on digitalized OPG images [47]. However, other three tooth extraction trials showed no significant difference in bone formation between PRF and blank control groups [48, 49] or between PRF and PRP on radiographic evaluation [50]. In controlled trials of inflammation-induced bone defect, two randomized controlled trials (RCTs) [51, 52] proved that PRF enhanced bone fill in IBD compared with open flap debridement (OFD) only.…”
Section: Effect Of Prf On Human Oral and Maxillofacial Bone Regenementioning
confidence: 99%
“…By contrast, Doiphode et al. ( 41 ) concluded that alveolar ridge resorption may be reduced, and bone formation may be promoted by PRF.…”
Section: Discussionmentioning
confidence: 95%